Emotional impact of clinical practice in Burns Unit among nursing students: a qualitative study - Caminati, Gloria; Cappelli, Lucia; Ferri, Paola; Artioli, Giovanna; Spadola, Milena; Spadola, Milena; Vecchiatini, Moira; Melotto, Martina; Di Lorenzo, Rosaria; Rubbi, Ivan (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. In Burns Units, the long professional relationship with patients suffering from intense physical pain and psychological distress, which cannot be completely resolved or minimized, exposes nurses to very intense emotions and stressful experiences. Learning to care for patients with such medical conditions can arouse many emotions also in nursing students, that can be both positive and negative. The goal of this study was to describe the emotional impact experienced by nursing students in a Italian Burns Unit.Methods. A qualitative research was implemented among 16 undergraduate nursing students, before and after clinical practice in a Burns Unit, through a semi-structured interview.Results. Strong and conflicting emotions from nursing students were reported in the preliminary stage of the internship. Their enthusiasm and curiosity for a new opportunity countered their fear and anxiety of not feeling able to deal with the clinical situation. The internship experience ranged from emotions of joy at the healing of patients to impotence and frustration at not being able to alleviate intense and lasting suffering. All students reported that the internship was experienced as an important opportunity for personal and professional growth.Conclusions. In light of the results, we highlight that nurse trainers should support students to take full advantage of this training, helping them to express their emotions and, in the same time, to learn to manage them profitably.